Redistribusi Tanah Bekas Hak Erfpacht Dalam Kaitannya Dengan Pilot Project Of Agrarian Reform Guna Mewujudkan Sustainable Development Di Desa Galengdowo, Kabupaten Jombang - Fernanda, Fadila; Kartika, Adhitya Widya (UI Scholars Hub, 2022)
The redistribution of land with erfpacht right in Galengdowo village is one of the agrarian reform programs in the form of distributing state land to cultivators by giving ownership right to the land they cultivate. These freehold land certificates can then be used as collateral to obtain business capital through Community Land Empowerment (CLE) which is aimed at becoming a pilot project for an agrarian reforma village producing coffee and dairy products by developing regional-level businesses to become national scale. This study uses an empirical legal research method that examines the implementation of law in society. The approach used is a qualitative approach based on primary, secondary and tertiary legal sources. The results of this study explain that the implementation of the redistribution of erfpacht title land in Galengdowo village has met conformity based on laws and regulations so that the land redistribution program can be said to have provided legal certainty and benefits to the people of Galengdowo village. mainly in the increase in revenue up to 125.7%. The implementation of the redistribution of erfpacht title land in Galengdowo village also encountered a number of obstacles, but these obstacles could be overcome properly through ideas from the Central and Regional Governments.